A General Vapor‐Induced Coating Approach for Layer‐controlled Organic Single Crystals. (11th January 2023) - Chen, Shengnan; Liu, Zhaoxin; Long, Haoran; Yang, Jiaxin; Li, Zheng; Cai, Zheren; Qu, Zhiyuan; Shao, Lujing; Shi, Xiaosong; Jiang, Lang; Xu, Wei; Dong, Huanli; et al.
Abstract: 2D organic semiconductor crystals (2D OSCs) are vital for high‐performance electronic and optoelectronic devices owing to their unique material merits. However, it is still challenging to fabricate high‐quality and large‐scale ultrathin 2D OSCs with controllable molecular layers due to the disordered molecular deposition and uncontrollable mass transport in solution‐processing fabrication. Here, a vapor‐induced meniscus modulating strategy for preparing unidirectional and stable Marangoni flow to guide contactless meniscus evolution is reported, which ensures uniform mass transport and ordered molecular deposition to achieve high‐quality ultrathin 2D OSCs. Both the surface tension difference and the substrate wettability are critical to meniscus formation, which results in various meniscus deformation states and film morphologies. Based on the optimized vapor‐solvent system, ultrathin 2D OSCs of C8 ‐BTBT with precise layer definition are prepared controllably. The discrepancies in liquid film height and solute concentration are decisive in controlling the molecular scale thickness ranging from mono to a few layers. Moreover, the layer‐dependent electronic and optoelectronic properties of the ultrathin films are systematically investigated. Notably, high‐performance polarization‐sensitive solar‐blind photodetectors are achieved with a dichroic ratio of photocurrent up to 2.26, and the corresponding polarimetric image sensor exhibits superior solar‐blind polarization imaging capability thanks to the high crystalline quality. Abstract : A vapor‐induced meniscus modulating approach is proposed for producing unidirectional and stable Marangoni flow to achieve high‐quality ultrathin 2D OSCs with precise layer definition, ensuring uniform mass transport and ordered molecular deposition. The solar‐blind polarized imaging capability is evaluated by fabricating a polarimetric image sensor array, which exhibits superior polarization imaging ability.